A Solid‐State Intramolecular Wittig Reaction Enables Efficient Synthesis of Endofullerenes Including Ne@C60, 3He@C60, and HD@C60. Issue 16 (4th March 2021) - Hoffman, Gabriela; Walkey, Mark C.; Gräsvik, John; Bacanu, George R.; Alom, Shamim; Bloodworth, Sally; Light, Mark E.; Levitt, Malcolm H.; Whitby, Richard J.
Abstract: An open‐cage fullerene incorporating phosphorous ylid and carbonyl group moieties on the rim of the orifice can be filled with gases (H2, He, Ne) in the solid state, and the cage opening then contracted in situ by raising the temperature to complete an intramolecular Wittig reaction, trapping the atom or molecule inside. Known transformations complete conversion of the product fullerene to C60 containing the endohedral species. As well as providing an improved synthesis of large quantities of 4 He@C60, H2 @C60, and D2 @C60, the method allows the efficient incorporation of expensive gases such as HD and 3 He, to prepare HD@C60 and 3 He@C60 . The method also enables the first synthesis of Ne@C60 by molecular surgery, and its characterization by crystallography and 13 C NMR spectroscopy. Abstract : Solid‐state filling of a stable phosphorus ylid open‐cage fullerene is followed by heating, inducing an in situ intramolecular Wittig reaction to reduce the size of the cage opening and trapping a single gas atom or molecule inside. Expensive gases can be compressed to high pressure, leading to high incorporation of the endohedral species. Cage closure steps allow preparation of gram‐scale endohedral fullerenes including 3 He@C60, HD@C60, and Ne@C60 .